Creep properties of a U‐type notch plate in Ni‐based superalloy. Issue 11 (14th November 2019) - Gan, W.; Wen, Z.; Pei, H.; Gao, H.
Abstract: In the present investigation, the effect of notch on creep rupture behavior and creep rupture life of a Ni‐based superalloy has been assessed by performing creep tests on smooth and U‐notched plate specimen under 0°C. The finite element analysis coupled with continuum damage mechanics are carried out to understand the stress distribution across the notch throat and the creep damage evolution under multi‐axial stress state. The creep rupture life of U‐notched specimen is much larger than that of plane plate specimen under the same stress condition, indicating that there is a strengthening effect on notch specimen. Creep rupture life increases with increasing the notch radius, the smaller notch radius can induce the creep rupture easier. The effect of notch on the creep damage is also studied. It is found that the location of the maximum creep damage and the maximum equivalent creep strain initiates first at the notch root and gradually moves to the inside as the notch radius increases.